Fish digestive lipase quantification methods used in aquaculture studies - Nolasco-Soria, Héctor (Frontiers in Aquaculture, 2023)
The content of fats or oils in natural or artificial feed is generally 6 to 20%-30% since they are essential to cover fish's energetic and structural requirements. Therefore, studies of the ontogeny or response of lipase activity to food treatments are widespread. A systematic review of the articles published on lipase activity in fish in aquaculture was carried out over five years (2016 - 2020); it was only taken as a representative example. Any period between 2010-2022 would be similar to show the actual lipase method used. As a result of this review, it was found that the methods used by the authors are very varied and have significant differences in the type of substrate, substrate concentration, bile salt type and concentration, pH, temperature, incubation time, measurement of hydrolysis products, and definition of lipase units. The above does not mean it is incorrect but it significantly limits comparative studies. The most used methods (with p-nitrophenyl derivates, β-naphthyl derivates, and emulsified natural oils as substrates) can be selected to redesign the determination under temperature, pH, ion, and bile salt conditions closer to fish physiology (or lipase response), and using the appropriate standard curves or the corresponding molar extinction coefficient for the definition of the lipase units. Standardizing current lipase analytical procedures should improve the reliability of comparative studies of aquaculture fish species.